2017
DOI: 10.1017/s1751731117000787
|View full text |Cite
|
Sign up to set email alerts
|

The effects of fermentation and enzymatic treatment of pea on nutrient digestibility and growth performance of broilers

Abstract: The present study examined the impacts of native, fermented or enzymatically treated peas (Pisum sativum L.) inclusion in broiler diets, on growth performance and nutrient digestibility. For the fermentation process, Madonna pea was mixed with water (1/1) containing 2.57 × 10 8 Bacillus subtilis (GalliPro ® ) spores/kg pea and then, incubated for 48 h at 30°C. For the enzymatic treatment process, the used water for dough production contained three enzymes, AlphaGal TM (α-galactosidase), RONOZYME ® ProAct and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Protease and ZZUPF95 + Protease groups held the more significant effect on the degradation of large protein molecules compared with that of SBM, CK and ZZUPF95, and the degradation effect was more obvious in the aerobic exposure of ZZUPF95 + Protease group. The mixed group fermented SBM by LAB with complementary protease to synergistically degrade large molecule proteins in feed ingredients into small molecule peptides that can be easily absorbed by animals, thereby increasing the nutritional value and conversion rate of feed [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protease and ZZUPF95 + Protease groups held the more significant effect on the degradation of large protein molecules compared with that of SBM, CK and ZZUPF95, and the degradation effect was more obvious in the aerobic exposure of ZZUPF95 + Protease group. The mixed group fermented SBM by LAB with complementary protease to synergistically degrade large molecule proteins in feed ingredients into small molecule peptides that can be easily absorbed by animals, thereby increasing the nutritional value and conversion rate of feed [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the effect of soyabean meal co-fermented by protease and probiotics was shown to be superior to single fermentation or enzymatic process in broilers (Cheng et al, 2019). It has also been reported that, from the perspective of nutrition, the proportion of nutrients, and especially amino acids proportion of some inexpensive and single protein feed materials, becomes balanced after the co-fermentation by B. subtilis, protease and pectinases (Goodarzi Boroojeni et al, 2017;.…”
Section: Purpose Of Microbe and Enzyme Cooperationmentioning
confidence: 99%
“…xylanase (Chu et al, 2017) Palm kernel (Trachycarpus fortunei) cake Lactobacillus plantarum (Lee et al, 2019), Paenibacillus curdlanolyticus (Alshelmani et al, 2014) hemicellulase (xylanase, mannanase), cellulase, proteolytic (endoprotease) (Lee et al, 2019;Olukomaiya et al, 2019) Peas (Pisum sativum L.) Bacillus subtilis, Bacillus licheniformis (Goodarzi Boroojeni et al, 2017; α-glucosidase, protease, pectinase (Goodarzi Boroojeni et al, 2017; Barley (Hordeum vulgare L.) Lactobacillus plantarum, Rhizopus oryzae (Wang et al, 2019), lacto-acid bacteria (Yasar and Tosun, 2018) glucoamylase (Wang et al, 2019), cellulose (Yasar and Tosun, 2018) Grain (Olyza sativa L.) by-product Pediococcus acidilactici (Bartkiene et al, 2018) xylanase, cellulase, β-glucanase (Bartkiene et al, 2018) Potatoes (Solanum tuberosum L.) Lactobacillus plantarum (Du et al, 2018) cellulose (Du et al, 2018) Maize (Zea mays L.) stalk Chaetomium, white-rot fungi, Lactobacillus plantarum (Atuhaire et al, 2016), Bacillus licheniformis (Alokika and Singh, 2019) cellulase, xylanase (Alokika and Singh, 2019) Maize (Zea mays L.) cob Bacillus subtilis (Jia et al, 2017), Bacillus licheniformis, Lactobacillus plantarum, Saccharomyces cerevisiae (Alokika and Singh, 2019) xylanase (Alokika and Singh, 2019), cellulase, hydrolysis enzyme (Jia et al, 2017) Alfalfa (Medicago sativa L.) Lactobacillus plantarum, Pediococcus pentosaceus (Chen et al, 2019), yeast, lacto-acid bacteria (Ding et al, 2013), Lactobacillus buchneri (Kung et al, 2003) cellulase, hemicellulose (Chen et al, 2019), viscozyme (Schmidt et al, 2001), plant enzyme (Ding et al, 2013), β-glucanase, α-amylase, xylanase, and galactomannase (Kung et al, 2003) Blood meal Bacillus subtilis…”
Section: Substrates Microorganisms Strains and Enzymesmentioning
confidence: 99%
“…It has been reported that bacterial fermentation results in the production of a considerable amount of lactic acids, which would retard harmful bacterial multiplication in the gut, minimize nutrient and dry matter (D.M.) loss during storage, and boost the palatability of the diet to the animal [11,12].…”
Section: Introductionmentioning
confidence: 99%